Assessing the cost-benefit effect of a plasmodium falciparum drug resistance mutation on parasite growth In vitro - Froberg, Gabrielle (2018)
Plasmodium falciparum mutations associated with antimalarial resistance may be beneficial for parasites under drug pressure, although they may also cause a fitness cost. We herein present an in vitro model showing how this combined effect on parasite growth varies with the drug concentration and suggest a calculated drug-specific cost-benefit index, indicating the possible advantage for mutated parasites. We specifically studied the D-to-Y change at position 1246 encoded by the pfmdr1 gene (pfmdr1 D1246Y) in relation to amodiaquine resistance. Susceptibilities to amodiaquine, desethylamodiaquine, and chloroquine, as well as relative fitness, were determined for two modified isogenic P. falciparum clones differing only in the pfmdr1 1246 position. Data were used to create a new comparative graph of relative growth in relation to the drug concentration and to calculate the ratio between the benefit of resistance and the fitness cost. Results were related to an in vivo allele selection analysis after amodiaquine or artesunate-amodiaquine treatment. pfmdr1 1246Y was associated with decreased susceptibility to amodiaquine and desethylamodiaquine but at a growth fitness cost of 11%. Mutated parasites grew less in low drug concentrations due to a predominating fitness cost, but beyond a breakpoint concentration they grew more due to a predominating benefit of increased resistance. The cost-benefit indexes indicated that pfmdr1 1246Y was most advantageous for amodiaquine-exposed parasites. In vivo, a first drug selection of mutant parasites followed by a fitness selection of wild-type parasites supported the in vitro data. This cost-benefit model may predict the risk for selection of drug resistance mutations in different malaria transmission settings.